Exploring the potential of signalling molecules hydrogen sulfide and nitric oxide in augmenting salt stress resilience in bitter gourd - Ritu Kumari; Gurmeen Rakhra; Abdulaziz Abdullah Alsahli; Javaid Akhter Bhat; Parvaiz Ahmad (BMC Plant Biology)
Abstract Salinity stress is a major abiotic factor limiting plant growth and productivity by disrupting key physiological and biochemical processes and inducing excessive accumulation of reactive oxygen species (ROS), which cause oxidative damage to cellular structures. To combat ROS, signalling molecules such as hydrogen sulfide (H₂S) and nitric oxide (NO) play crucial roles in modulating antioxidant defence systems and enhancing stress tolerance in plants. Although the individual roles of hydrogen sulfide (H₂S) and nitric oxide (NO) in stress responses have been explored, their interactive effects and signalling crosstalk under salt stress remain inadequately understood, particularly in cucurbit crops. Therefore, this study aims to established to role of exogenous application of H₂S and NO, alone or in combination, would mitigate salt-induced oxidative stress and improve growth performance in bitter gourd (Momordica charantia) seedlings through modulation of antioxidant defence mechanisms. To test this, bitter gourd seedlings were treated with NaCl (25 mM) alone or in combination with NaHS (40 µM, H₂S donor), SNP (90 µM, NO donor), and their respective scavengers and inhibitors (cPTIO and L-NAME = 100 µM). Results revealed that NaCl stress reduced fresh weight, dry weight, and plant height by 19%, 22%, and 18.9%, respectively, compared to control. It also decreased photosynthetic pigment contents and elevated oxidative stress markers, including H₂O₂, superoxide radicals (O₂•⁻), and malondialdehyde (MDA) and enzymatic activities. Exogenous application of NaHS and SNP, both individually and in combination, mitigated the adverse effects of salinity. Importantly, these mitigating effects were suppressed when cPTIO (NO scavenger) and L-NAME (NO synthase inhibitor) were applied, confirming the involvement of NO-mediated signalling in H₂S-induced stress tolerance. Thus, the findings demonstrate that H₂S significantly collaborates with NO to alleviate the negative impacts of salinity by modulating antioxidant defence and reducing oxidative damage in bitter gourd seedlings. Graphical Abstract